Plasmonic crystals for strong light-matter coupling in carbon nanotubes - Zakharko, Yuriy; Graf, Arko; Zaumseil, Jana (Nano letters, 2016)
Their high oscillator strength and large exciton binding energies make single-walled carbon nanotubes (SWCNTs) highly promising materials for the investigation of strong light-matter interactions in the near infrared and at room temperature. To explore their full potential, high-quality cavities—possibly with nanoscale field localization—are required. Here, we demonstrate the room temperature formation of plasmon-exciton polaritons in monochiral (6,5) SWCNTs coupled to the subdiffraction nanocavities of a plasmonic crystal created by a periodic gold nanodisk array. The interaction strength is easily tuned by the number of SWCNTs that collectively couple to the plasmonic crystal. Angle- and polarization resolved reflectivity and photoluminescence measurements combined with the coupled-oscillator model confirm strong coupling (coupling strength ∼120 meV). The combination of plasmon-exciton polaritons with the exceptional charge transport properties of SWCNTs should enable practical polariton devices at room temperature and at telecommunication wavelengths.
Gesehen am 01.10.2021